A Preliminary Study : The Urgency of Scientific Paper of Science Teacher - Rahmah Evita Putri (Fakultas MIPA Universitas Negeri Padang, 2020)
PP No. 74 of 2008 states that salary is the right that is received by the teacher for his work from the education provider or education unit in financial form on a regular basis in accordance with statutory regulations. Based on Ministerial Regulation (Permen) no. 19 of 2009 which states that promotion or class must use scientific work, and it would be better if the scientific work can be published, where one of the scientific works that can be made by teachers can be Classroom Action Research (CAR), where research should not foreign to the teacher, where by researching the teacher can really solve a problem that occurs in students who are in the teacher's education, however, if it only stops until writing a CAR report, of course the results of the research will be unfortunate because it is not published, so that it cannot be a reference for further research or cannot motivate teachers from other regions to carry out research. By writing scientific articles and publishing these articles in scientific journals nationally and internationally it will certainly be able to share knowledge for allied researchers and be a motivation for other teachers to carry out research and publish the results of the research. The results of the field research show that science teachers are still very taboo about writing scientific articles, especially the publication of scientific articles that have been made. The survey shows that only a portion of natural science teachers have implemented CAR, and less than a quarter of these teachers have written scientific articles. It can be concluded that writing scientific articles is very much needed and must be carried out by teachers especially science teachers. So that later teachers can always carry out research on a regular basis.